Aplikasi Teknologi Mikroenkapsulasi dalam Meningkatkan Stabilitas dan Efektivitas Bahan Aktif pada Produk Kosmetik: Kajian Literatur - Feggy Yustika Sitinjak; Arif Budiman; Diah Lia Aulifa; Santi Sinala (Direktorat Politeknik Kesehatan Makassar, 2025)
The cosmetics industry is growing rapidly in line with increasing public awareness of the importance of skin care and optimal appearance. Cosmetic products not only serve an aesthetic purpose but also protect the skin from external factors such as UV rays, aging, and pollution. Although many studies have discussed the advantages of microencapsulation, few have analyzed its application in finished cosmetic products. Therefore, this study aims to provide a deeper understanding of the application of microencapsulation in enhancing the stability and efficacy of active ingredients in cosmetic products. This review employs a literature review method based on nine selected scientific articles from national and international journals. Literature searches were conducted using PubMed and Google Scholar with keywords related to microencapsulation in cosmetic products. The results of the study indicate that microencapsulation can enhance the stability of active ingredients, protect them from degradation caused by environmental factors, and enable controlled release of active ingredients. Cosmetic products such as sunscreen gel, face cream, and blush have been successfully developed using microencapsulation technology. Additionally, microencapsulation improves user comfort by reducing unwanted odors or colors and minimizing the risk of skin irritation. This review also identifies technical limitations in microencapsulation methods and provides recommendations for further research to improve the application of this technology in the cosmetics industry for greater efficiency and sustainability. In conclusion, microencapsulation is an effective solution for enhancing stability, efficacy of active ingredients, and user experience quality in cosmetics. Keywords: Cosmetic applications, efficacy, microencapsulated cosmetics, microencapsulation methods, stability